Analysis of the Effect of Mudharabah Financing, Musyarakah Financing, and Murabahah Receivables on the Net Profit of the Islamic Banking Industry - Maya Novita Sari; Lestari Wuryanti; Anita (International Journal of Management, Economic and Accounting, 2026)
This study aims to analyze the influence of mudharabah, musyarakah, and murabahah financing on the net profit of the Islamic banking industry in Indonesia during the 2020–2024 period. The research sample was selected using the purposive sampling method and included six Sharia Commercial Banks that consistently published complete financial statements during the study period. The data used is secondary data, while the analysis techniques applied include panel data regression with the selection of the best model through Chow, Hausman, and Lagrange Multiplier tests. The results of the study show that mudharabah financing has a significant influence on net profit, musyarakah financing shows a influence, but it is not statistically significant on net profit, while murabahah receivables are proven to have a significant influence on net profit. Simultaneously, these three types of financing have a significant effect on the net profit of the Islamic banking industry, indicating that proper financing portfolio management can contribute to increasing bank profitability.